Annona muricata Leaf as an Anti-Cryptosporidial Agent: An In Silico Molecular Docking Analysis and In Vivo Studies - Eman S. El-Wakil; Hagar F. Abdelmaksoud; Majed H. Wakid; Muslimah N. Alsulami; Olfat Hammam; Haleema H. Albohiri; Marwa M. I. Ghallab (MDPI AG, 2023)
Cryptosporidiosis is a serious parasitic diarrheal disease linked to the occurrence of colorectal cancer in immunocompromised patients. The FDA-approved drug nitazoxanide (NTZ) achieved a temporary effect, and relapses occur. Annona muricata leaf is widely used in traditional medicine to treat a wide range of disorders, including antiparasitic and anticancer effects. So, this study aimed to investigate Annona muricata leaf antiparasitic and anticancer properties compared to NTZ in Cryptosporidium parvum (C. parvum) acutely and chronically infected immunosuppressed mice. A molecular docking analysis was performed to evaluate the effectiveness of some biologically active compounds that represented the pharmacological properties of Annona muricata leaf-rich extract toward C. parvum lactate dehydrogenase compared to NTZ. For the in vivo study, eighty immunosuppressed albino mice were classified into four groups as follows: group I: infected and treated with A. muricata; group II: infected and treated with nitazoxanide; group III: infected and received no treatment; and group IV: were neither infected nor treated. Furthermore, half of the mice in groups I and II received the drugs on the 10th day post-infection (dpi), and the other half received treatment on the 90th day post-infection. Parasitological, histopathological, and immunohistochemical evaluations were performed. The docking analysis showed that the lowest estimated free energy of binding of annonacin, casuarine, L-epigallocatechin, P-coumaric acid, and ellagic acid toward C. parvum LDH, were −6.11, −6.32, −7.51, −7.81, and −9.64 kcal/mol, respectively, while NTZ was −7.03 kcal/mol. Parasitological examination displayed a significantly high difference in C. parvum oocyst mean counts in groups I and II compared to group III (p-value < 0.001), with group I demonstrating the highest efficacy. The analyses of histopathological and immunohistochemical results revealed that group I showed restoration of the normal villous pattern without evidence of dysplasia or malignancy. A. muricata leaf has proved to be a reliable agent for Cryptosporidium treatment. This paper argues for its promising use as an antiparasitic agent and for the prevention of neoplastic sequels of Cryptosporidium infection.